2016
DOI: 10.7567/jjap.55.08na03
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in local work function as an origin of moiré contrast in scanning tunneling microscopy images of Pb thin films/Si(111)

Abstract: By scanning tunneling microscopy (STM), we measured an evolution of electrical conductance from the tunneling to point contact regimes on Pb thin films formed on a Si(111) substrate. Immediately before the contact formation, the conductance evolution curves exhibit an onset of the conductance that is presumably due to a short-range chemical interaction between the tip apex atom and surface atom(s), and we found that the onset can be utilized as a reference of the tip–sample distance. By measuring the spatial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Electrons in metallic films with free-electron property, atomic-scale flatness, and nanometer thickness can lead to the quantization of the electron wave vector to form the quantum well (QW) states in the surface normal [4][5][6][7][8][9][10][11][12][13][14]. Yang et al demonstrated that the image potential in vacuum provides a phase contribution on empty QW states, causing the energy spacing between adjacent states to shrink [16].…”
Section: Introductionmentioning
confidence: 99%
“…Electrons in metallic films with free-electron property, atomic-scale flatness, and nanometer thickness can lead to the quantization of the electron wave vector to form the quantum well (QW) states in the surface normal [4][5][6][7][8][9][10][11][12][13][14]. Yang et al demonstrated that the image potential in vacuum provides a phase contribution on empty QW states, causing the energy spacing between adjacent states to shrink [16].…”
Section: Introductionmentioning
confidence: 99%
“…Determining work function variations in nanoscale structures by field emission resonance (FER) spectroscopy has been widely used in STM. , Briefly, in FER the bias voltage between the STM tip and the sample surface is chosen such that the Fermi level of the STM tip lies above the vacuum level of the sample. In this Fowler–Nordheim tunneling regime, the drop in the potential at the tunnel junction causes a potential well between the tip and the sample surface.…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish strong work function modulations in the moiré structures, the interlayer charge redistribution must depend on local interlayer atom coordination within the moiré unit cell. This has been shown for monolayer materials deposited on crystalline supports such as NaCl, FeO, , or Pb monolayers on silver, platinum, or silicon crystals, respectively. More prominently this effect has been also explored for graphene on Rh or h-BN on various transition metals (e.g., Rh, Ru, Cu, , Ir) where the varying coordination of the BN atoms with respect to the surface metals gives rise to strongly variable chemical interactions, causing large corrugation of the h-BN layer and consequently modulations of interlayer dipoles and the local work function .…”
mentioning
confidence: 99%